Implementation of a multi-stage double-slope solar still for salt and distilled water production under tropical rainy conditions - Ismail, Nova Risdiyanto; Suwandono, Purbo; Hermawan, Dadang; Anggraeni, Frida Dwi; Akbar, Dzulfikar Johan (Eastern-European Journal of Enterprise Technologies, 2026)
The object of this study is a multi-stage double-slope solar still used for simultaneous distilled water production and seawater concentration into salt crystals under tropical rainy conditions. The problem solved in this study is the discontinuity of conventional salt production during the rainy season, when open evaporation ponds become less effective because of rainfall, high humidity, and unstable solar radiation. Experiments were conducted in Malang as a laboratory environment and in Lamongan as a coastal salt production area. The results showed that the system could operate continuously during the rainy season and increase seawater salinity from 3.5% to about 29%. The cumulative distilled water production was almost identical in both locations, reaching 36.57–36.58 L/m2. However, seawater concentration was faster in Malang, requiring 25 days, compared with 29 days in Lamongan. This difference was explained by the larger temperature gradients between water, fins, glass cover, and ambient air in Malang, which improved evaporation and condensation. Salt from Malang also had higher NaCl content, 92.33%, than salt from Lamongan, 86.95%, supported by lower Mg and S contents. FTIR detected O–H, sulfate, and carbonate groups, while XRD confirmed halite as the dominant crystalline phase. Macro images showed that Malang salt crystals were more uniform and regular. The distinctive feature of the system is the tiered double-slope configuration, which enables gradual brine concentration while still producing distilled water in a closed solar-driven process. These results show that the system can be practically applied in tropical coastal salt-producing areas with high rainfall to support more continuous salt and distilled water production